(untitled) (Altre Modernità, 2021)
Anima, by Lebanese-born Canadian-raised author Wajdi Mouawad, is a road novel that takes the reader through different locations on the North American continent in order to explore the darkest side of humankind. This approach will focus on the provocative narrative technique used by Mouawad, filtered through the eyes of a significant number of animals and insects, in order to consider the different representations of vulnerability that articulate the text. In the novel, animals and insects are not only the narrators but also fundamental characters. As this analysis will show, their vulnerability represents the uncertainty of fate in contemporary society, being in the hands of those apparently superior creatures that decide when they can live and when they have to die. As an example of a vulnerable text, Anima relies on the theatricality of this animal Greek chorus to represent the need for humans to undergo a process of animalization. The protagonist, Wahhch Debch, reaches a stage of symbiosis with his animal side that allows him to transcend his vulnerability as a child refugee and as an adult who lost his wife, and this new sense of animal self serves him as an empowering element to break ties with his past.